Pemahaman HIV/AIDS di Lingkungan Keluarga Melalui Sumber Daya Manusia dalam Menciptakan Keluarga Sakinah - Soleha, Soleha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
HIV/AIDS has become a global issue in our life. Looking at the various cases of HIV/AIDS happening in society, this problem is not just a health issue, but the impact will cause other problems, such as social and economic problems for patients and their families. Therefore, the participation of stakeholders in overcoming HIV/AIDS problems is very important. To optimize efforts in combatting HIV / AIDS in Indonesia, it requires the involvement from various sectors both government and non-governmental organizations. The family life which is based on the Islamic values as a religion that brings together men and women in legal matrimony has a very important role in creating a culture of social order of the good society